Factors Relating To The Spirituality Of Students/I Ners Level Ii During The Covid-19 Pandemic Stikes Santa Elisabeth Medan, 2021 - Imelda Derang; Lindawati Simorangkir; Nince Junita Waruwu (Science Midwifery, 2022)
The Covid-19 pandemic is a problem that has spread throughout the world, including in Indonesia and is experiencing continuous improvement. Spirituality is a person's belief in a greater power which is a source of strength for each individual so that it motivates individuals to be closer and creates love for themselves. themselves, others, God and the environment. The purpose of this study was to determine the relationship between self, others, God and the environment with the spirituality of level II students during the Covid-19 pandemic at Stikes Santa Elisabeth Medan in 2021. The method used an analytical research design using a cross sectional approach. The sample in this study was 88 respondents. The sampling technique was total sampling. The instrument used is a questionnaire. The results of the chi - square statistical test obtained p - value = 0.001 (p < 0.05), so there is a significant relationship between self, others, God and the environment with spirituality. Data analysis using multiple logistic regression test. The results of this study obtained one subvariable that is most related to spirituality, namely the God factor (p-value 0.033 <0.05). God factor with a B coefficient of 0.033 and exp (B) of 21.0. This means that students with God's factors that support 21 times will have high spirituality compared to God's factors that do not support them. It is hoped that students will be able to improve their spirituality by reflecting on the meaning of life, doing good to others selflessly, having high belief in God and participating in social service activities in the community.